The Jajarkot Earthquake: Revealed the Vulnerability of Load Bearing Structures in Western Nepal - Poudel, Hemanta Raj; Chaulagain, Hemchandra (Himalayan Journal of Applied Science and Engineering, 2024)
The Jajarkot Earthquake, which occurred on 3rd November, 2023 of magnitude 5.7 (Mw) exposed Nepal’s longstanding vulnerability to seismic activity. This paper presents damage assessments derived from both on-site field observations and secondary resources to evaluate the damages sustained by load bearing masonry structures. In the region, 95% of the building structures are based on masonry construction. The damage status of structures in Jajarkot and Rukum East highlighted that about 50% of the building structures were partially and complete damage. The evaluation encompassed various aspects, including the types, mechanisms, and underlying causes of the damage incurred by structures. The observed damage was categorized using an established catalogue originally developed for the identification of failure mechanisms and vulnerability assessment. The common types of damage encompassed features like cracks in the load bearing external walls and corners, diagonal cracks originating from door and window corners, vertical out-of-plane displacement of external walls, collapse of external walls, and partial collapse of load bearing internal walls, fracturing of window and door lintels and complete collapse of structure. Some special forms of damage which was of new nature and distinct from those observed in prior seismic events such as the Gorkha earthquake included ruptures in the outer surfaces of loadbearing external walls, partial roof structure collapses, out-of-plane fragmentation or disintegration as well as rupture. The causes underlying this general damage were attributed to irregular bonding systems, weak mortar, stone block formation, size of stone blocks, absence of tie beams, weakly connected corners, insufficient connections of wall-roof and wall-floor systems, and differing internal wall systems. The mechanisms of damage varied based on the number and specifics of these causative factors, as well as certain structural attributes.